A study on Calf’s Behavior and Growth Performance in Relation to Gestation Period and Lactation Season - Hesham Hosny Mohammed (South Valley University, 2018)
The present study aimed to assess the impact of the length of the gestation period (GPL) and a number of lactation season of cows on behavior and growth performance in calves from birth until weaning. The presence of abnormal behavior during 1st twelve hours of the calf's life as delayed Sternal recumbency and standing or abnormal suckling was not significantly affected by GPL. Also, the duration and frequency of behavior related to respiratory, digestive or mixed disorders had a non-significant variation between groups of different gestation period length. However, the increase in GPL had the lowest percentage and duration of behavior related to respiratory and digestive disorders. Calves with the longest GPL had a significantly higher birth weight and it had a significant effect on pre-weaning growth rate. On the other side, the presence of abnormal behavior during the first twelve hours of the calf's life as delayed Sternal recumbency and standing or abnormal suckling were higher in 3rd parity. The number of lactation season had no significant effect on the duration and frequency of behavior related to respiratory, digestive or mixed disorders. The birth weight of calves was higher in the third parity group (36.73 kg) than other parities, but the differences didn't reach the significance, moreover, the weaning age and pre-weaning growth rate did not affect by the lactation season number. There was a negative correlation between abnormal behavior and the pre-weaning growth rate. There was a positive correlation between duration of abnormal behavior and the weaning age.